The Interpretations of Don Quixote in the Russian Poetry of 1960s–1970s - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2014)
The aim of the article is to interpret poems concerning Don Quixote written by contemporary Russian poets, like Iosif Brodsky, Alexander Kushner, Vsevolod Rozhdestvensky, Robert Rozhdestvensky, David Samoilov and many others, with the view to showing how the Spanish literary figure transforms in the receiving culture into an (indigenized) philosophical category.The author sets out to identify the main semantic constants of the Russian Don Quixote, to show an evolution of the hero in the oeuvre of particular poets (Pavel Antokolsky and Zinovy Valshonok) and to indicate the relationship between the image of Don Quixote and the lyrical subject. She also examines the relationship between Don Quixote and Sancho Panza and, finally, explains political connotations of the figure of Don Quixote in the poems by Margarita Aliger and Yevgeny Dolmatovsky.